2010
DOI: 10.1007/s12519-010-0028-z
|View full text |Cite
|
Sign up to set email alerts
|

Congenital syphilis: still a serious, under-diagnosed threat for children in resource-poor countries

Abstract: Highlighting the variable picture of congenital syphilis, this report demonstrates how difficult it is to make a correct diagnosis by solely history and clinical presentation in a resource-poor setting. Hence false-positive and false-negative diagnoses are common, and clinicians have to maintain a high index of suspicion in diagnosing congenital syphilis. Therefore, an important approach to control and finally eliminate congenital syphilis as a major public health problem will be universal on-site syphilis scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 30 publications
0
16
0
6
Order By: Relevance
“…33,34 Additionally, there are approximately 1 million new cases of congenital syphilis annually warranting further research on risk factors for syphilis among women and identification and implementation of effective interventions. 35 Efforts to promote medical male circumcision should emphasize the other reproductive health benefits to men and their female partners, including syphilis prevention, in addition to HIV-1 prevention.…”
Section: Discussionmentioning
confidence: 99%
“…33,34 Additionally, there are approximately 1 million new cases of congenital syphilis annually warranting further research on risk factors for syphilis among women and identification and implementation of effective interventions. 35 Efforts to promote medical male circumcision should emphasize the other reproductive health benefits to men and their female partners, including syphilis prevention, in addition to HIV-1 prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Global incidence of congenital syphilis is estimated at 700,000–1.5 million cases per year (Krüger and Malleyeck, 2010). Resource-poor countries are disproportionately affected (Samuel et al, 2007), however, recent resurgences have been reported in nations such as China and Canada (Zhu et al, 2010).…”
Section: Systemic Diseases With Prominent Skin Manifestationsmentioning
confidence: 99%
“…I en retrospektiv studie fra Haydom-sykehuset i Tanzania beskrives 14 barn med medfødt syfilis (2). Den typiske hudreaksjonen ved sekundaer syfilis ble ikke sett hos barn yngre enn én måned, og diagnosen var da vanskelig fordi symptomene liknet neonatal sepsis.…”
Section: øKende Forekomst Av Medfødt Syfilis 1590unclassified